Pharmacogenomics Implementation: Considerations for Selecting a Reference Laboratory. Issue 9 (3rd September 2017) - Vo, Teresa T.; Bell, Gillian C.; Owusu Obeng, Aniwaa; Hicks, J. Kevin; Dunnenberger, Henry M.
Abstract : One of the initial steps for implementing pharmacogenomics into routine patient care is selecting an appropriate clinical laboratory to perform the testing. With the rapid advances in genotyping technologies, many clinical laboratories are now performing pharmacogenomic testing. Selection of a reference laboratory depends on whether a particular genotype assay is already performed by an internal health care organization laboratory or only available externally. Other factors for consideration are coverage of genomic variants important for the patient population, technical support, and cost. In some instances, the decision to select a particular reference laboratory may be the responsibility of the clinician who is recommending genomic interrogation. Only limited guidance is available that describes the laboratory characteristics to consider when selecting a reference laboratory. We provide practical considerations for selecting a clinical laboratory for pharmacogenomic testing broadly categorized into four domains: pharmacogene and variant selection; logistics; reporting of results; and test costs along with reimbursement.